Experimental observations of "reversible" transformation toughening. (15th January 2021) - Makkar, J.; Young, B.; Karaman, I.; Baxevanis, T.
Graphical abstract: Abstract: Materials with the propensity to undergo irreversible deformation display an increasing resistance to progressive crack advance, i.e., stable crack growth. A one-parameter description of stable crack growth by a fracture toughness vs. crack advance (resistance) curve is possible under specific conditions. Here, experimental observations are reported to (i) demonstrate that the toughness enhancement due to crack advance in hysteretic materials may be "reversed" by partial unloading, which has implications on the evaluation of the resistance curve and its validity conditions, and (ii) provide an experimental verification of the theoretical insight into the mechanics of stable crack growth.